Pengembangan Ekowisata Berkelanjutan dan Pemberdayaan Masyarakat: Studi Kasus Pusat Pendidikan Lingkungan Hidup di Desa Seloliman, Indonesia - Susiyanto Hendro Wiyono; Agus Subianto; Nuhman Nuhman (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
The ecotourism-based community empowerment model is designed to uplift local farmers by fostering the cultivation of organic agricultural plants and promoting sustainable ecotourism by utilizing natural resources and local cultural values. This study aims to illustrate the phenomenon within the community empowerment model for groups of organic farming practitioners engaged in ecotourism, as facilitated by the Center for Environmental Education (PPLH) Seloliman, Trawas, Mojokerto Regency. This study uses a qualitative descriptive approach to gather data through in-depth interviews, document analysis, focus group discussions, and field observations. The analysis reveals that the success in empowering local farmers is attributed to the maturity of ecotourism organizations and political development. Furthermore, the research findings indicate that economic empowerment has heightened farmers’ interest in cultivating organic rice due to its enhanced economic value. Simultaneously, social empowerment has broadened farmers’ perspectives, fostering openness to change and enabling them to interact and participate as surrogate hosts for ecotourism guests over a few days. This program carries implications for enhancing farmers’ understanding and commitment to leveraging natural resources and the environment. This study proposes that sustained ecotourism development necessitates a steadfast commitment to preserving environmental benefits and expanding the involvement of local communities. It is essential to uphold a cultural approach prioritizing sustainable ecotourism.